Effects of Soaking Time and Peppermint Oil Concentration on Chemical, Sensory, and Antibacterial Characteristics of Robusta Coffee (Coffea canephora) - Thaliarinanta, Angela Saraz; Kustyawati, Maria Erna; Hidayati, Sri; AS, Suharyono; Nurdin, Samsu Udayana (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2024)
The increase in public coffee consumption is influenced by lifestyle, technological support and the emergence of various choices of coffee. Herbal coffee is generally made by adding herbal powder, infusion, and drying. Soaking techniques with peppermint oil to make herbal coffee have never been studied. The purpose of this study was to determine the effect of robusta coffee treated with soaking time and peppermint oil concentration on chemical characteristics, sensory and antimicrobial activity. Randomized Complete Group Design method with two factors was performed in this study. The first factor is soaking time (L) which consists of 0 (L0), 5 (L1), and 10 (L2) min. The second factor was peppermint oil concentration consisting of 0% (K0); 0.5% (K1); and 0.75% (K2). The results showed that the soaking time and concentration of peppermint oil can increase the water content and pH. The peppermint coffee showed antimicrobial activity against Salmonella typhi and Eschericia coli bacteria with an inhibition diameter of 8.72-13.16 mm and 9.88-12.24 mm, respectively. The peppermint coffee of L1K1 treatment (5 min soaking time; 0.5% peppermint concentration), is preferred by panelists with sensory test scores on taste (6.15), aroma (7.09), aftertaste (5.32), and overall (6.16). Keywords: Coffee bean, Concentration, Peppermint oil, Robusta coffee, Soaking time.